Clinicopathological and survival outcomes of 4L lymph node dissection in left lung adenocarcinoma and squamous cell carcinoma - Shen, Leilei; Guo, Juntang; Zhang, Weidong; Liang, Chaoyang; Chen, Han; Liu, Yang (Frontiers in Oncology, 2023)
Background: Whether 4L lymph node dissection (LND) should be performed remains unclear and controversial. Prior studies have found that station 4L metastasis was not rare and that 4L LND may provide survival benefits. The objective of this study was to analyze the clinicopathological and survival outcomes of 4L LND from the perspective of histology. Methods: This retrospective study included 74 patients with squamous cell carcinoma (SCC) and 84 patients diagnosed with lung adenocarcinoma (ADC) between January 2008 and October 2020. All patients underwent pulmonary resection with station 4L LND and were staged as T1-4N0-2M0. Clinicopathological features and survival outcomes were investigated based on histology. The study endpoints were disease-free survival (DFS) and overall survival (OS). Results: The incidence rate of station 4L metastasis was 17.1% (27/158) in the entire cohort, with 8.1% in the SCC group, and 25.0% in the ADC group. No statistical differences in the 5-year DFS rates (67.1% vs. 61.7%, P=0.812) and 5-year OS rates (68.6% vs. 59.3%, P=0.100) were observed between the ADC group and the SCC group. Multivariate logistic analysis revealed that histology (SCC vs. ADC: OR, 0.185; 95% CI, 0.049–0.706; P=0.013) was independently associated with 4L metastasis. Multivariate survival analysis showed that the status of 4L metastasis was an independent factor for DFS (HR, 2.563; 95% CI, 1.282–5.123; P=0.008) but not for OS (HR, 1.597; 95% CI, 0.749–3.402; P=0.225). Conclusion: Station 4L metastasis is not rare in left lung cancer. Patients with ADC have a greater predilection for station 4L metastasis and may benefit more from performing 4L LND.